Fixed Point Theorems of the Iterated Function Systems (Communications in Mathematical Research, 2021)
In this paper, we present some fixed point theorems of iterated functionsystems consisting of $α$-$ψ$-contractive type mappings in Fractal space constituted bythe compact subset of metric space and iterated function systems consisting of Banachcontractive mappings in Fractal space constituted by the compact subset of generalized metric space, which is also extensively applied in topological dynamic system.